PROJECTION OF THE DYNAMICS OF ARABIC LITERATURE IN THE ERA OF SOCIETY 5.0 (International Conference on Social and Islamic Studies, 2022)
This article analyzes the dynamics of the growth of Arabic literature in the industrial era 4.0 and predicts its growth in the era of society 5.0. Based on a number of data it was found that even though Arabic is no longer the strongest language in international relations, it is still experiencing adjustments to the times, including in the industrial era 4.0. A number of indicators show that the dynamics of Arabic language and literature can survive and develop into the era of society 5.0, especially in terms of its use and utilization. If the principle of the industrial revolution 4.0 and the Era of Society 5.0 is the ability to adapt and improve human life, then the existence of Arabic literature enters cyberspace through a digitalization process that allows it to be read by the world community, even from this point of view it has developed from the previous era.